2011
DOI: 10.3354/dao02401
|View full text |Cite
|
Sign up to set email alerts
|

Injection of Acanthaster planci with thiosulfate-citrate-bile-sucrose agar (TCBS). I. Disease induction

Abstract: This is the first report of the successful induction of a transmissible disease in the coral-eating crown-of-thorns starfish Acanthaster planci (COTS). Injection of thiosulfate-citratebile-sucrose agar (TCBS) culture medium into COTS induced a disease characterized by discoloured and necrotic skin, ulcerations, loss of body turgor, accumulation of colourless mucus on many spines especially at their tip, and loss of spines. Blisters on the dorsal integument broke through the skin surface and resulted in large, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
31
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 46 publications
3
31
0
Order By: Relevance
“…4B) can be associated with the release of vibrio enterotoxins which are recognized for their capacity to induce intestinal fluid secretion, inflammation and severe tissue damage (Raimondi et al 2000, Thompson et al 2006. There was good agreement between the histopathology findings, bacterial culture and identification (Rivera-Posada et al 2011a,b, present study), suggesting that histopathological examination is a reliable tool that allowed identification of typical vibriosis lesions and could contribute to the differentiation from other causes. Varello et al (2008) compared histologic techniques and bacteria cultures for the diagnosis of bovine tuberculosis reporting similar results.…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…4B) can be associated with the release of vibrio enterotoxins which are recognized for their capacity to induce intestinal fluid secretion, inflammation and severe tissue damage (Raimondi et al 2000, Thompson et al 2006. There was good agreement between the histopathology findings, bacterial culture and identification (Rivera-Posada et al 2011a,b, present study), suggesting that histopathological examination is a reliable tool that allowed identification of typical vibriosis lesions and could contribute to the differentiation from other causes. Varello et al (2008) compared histologic techniques and bacteria cultures for the diagnosis of bovine tuberculosis reporting similar results.…”
Section: Discussionmentioning
confidence: 53%
“…The present study showed that bacteria assemblages found on affected COTS tissues played an important role in the development of disease supporting the hypothesis of activation of quorum sensing mechanism proposed by Rivera-Posada et al (2011a). However, being opportunistic species, vibrios can evolve and recombine when reaching high densities in animal guts or as part of aquatic biofilms, transferring or inducing expression of virulence genes in less or non-pathogenic populations (Thompson et al 2004).…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…Puncture wound from a spine is intensely painful and causes oedema, erythema and infection of the surrounding areas (Rivera-Posada et al 2011). Limiting the exposure of divers/collector to spines by injecting the organism with cheaper and environmental friendly chemicals (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, there are likely to be significant constraints on energy investement for CoTS towards the end of outbreaks following selection depletion of preferred coral prey (e.g., Acropora) if not comprehensive coral loss (Pratchett 2010). If crown-of-thorns starfish continue to invest disproportionately into immune defence even when prey are scarce, energy reserves will be depleted even more rapidly, thereby making individuals even more prone to disease (Rivera-Posada et al 2011b, 2011c. …”
mentioning
confidence: 99%